Strengthening the resilience of silvopastoralists through proven climate smart practices in the semi-arid region of Tunisia - Hassan, Sawsan; Jalali, Khalifa; Ouled Belgacem, Azaiez; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
Silvopastoral systems, integrating trees, shrubs, and livestock, offer an innovative approach to sustainable land use. Key to success is the strategic selection of forage crops, tailored to climatic and soil conditions, promoting system resilience and productivity. The field day showcased sustainable restoration practices, with farmers receiving Sulla seeds, marking a transformative step toward sustainable agriculture and improved economic well-being. A collaborative initiative in Tunisia led by ICARDA and the Direction Générale des Forêts de Tunisie, supported by the Livestock and Climate Initiative of the OneCGIAR, focuses on enhancing silvopastoral communities' livelihoods, emphasizing climate-smart practices. Success hinges on active stakeholder collaboration, participatory approaches, and addressing barriers like seed supply and technical knowledge.